2020
DOI: 10.29333/ejmste/7833
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Teaching Techniques and Scheme of Work in Teaching Chemistry in Rwandan Secondary Schools

Abstract: This study aims at determining the effect of the pedagogical technique most frequently used while implementing the competency-based curriculum (CBC) in teaching chemistry in senior two (S2) classes (age range 14-16) and the teachers' alignment with the scheme of work. It was conducted in 10 selected Rwandan secondary schools using a teacher survey, teacher interviews and the Classroom Observation Protocol for Undergraduate STEM (COPUS) in the period from 27 May to 8 July 2019. The result of the analysis reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 19 publications
4
27
0
1
Order By: Relevance
“…However, many teachers agreed on the statement (above 90%). This clearly showed that, even though teachers claim to use active learning methods, they still apply some passive teaching methods (Byusa et al, 2020a;Suhag et al, 2018)…”
Section: Classroom Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, many teachers agreed on the statement (above 90%). This clearly showed that, even though teachers claim to use active learning methods, they still apply some passive teaching methods (Byusa et al, 2020a;Suhag et al, 2018)…”
Section: Classroom Environmentmentioning
confidence: 99%
“…However, this was not the case as they only engage students in small group work activities, sometimes limited to a question and answer session. This provides no knowledge construction among students as they remain passive in the learning process (Byusa et al, 2020a;Nsengimana et al, 2017). The inability of teachers to use appropriate methods of instruction to teach chemistry that invariably translate to inadequate knowledge and skills to put in practice the learned material is becoming a challenge to the Rwandan educational system.…”
Section: Research Problemmentioning
confidence: 99%
“…The study done in optics (Ndihokubwayo et al, 2020), has found that Rwandan students have misconceptions related to light phenomena such as why the sky is blue and not violet, why we see things, and why the sunset or sunrise is red. These misconceptions take source from teachers who are still prioritizing passive learning (Byusa et al, 2020), where teachers present knowledge more than they guide students while students only listen to teachers and take notes. Thus, more effective instructional tools and active strategies are needed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study conducted in Rwanda informs that chemistry teachers prioritize group work-related activities ( Byusa et al., 2020 ). Teaching chemistry and the development of other expected learning outcomes to do with values and attitudes that are associated with the lesson taught as teachers try to meet the expectation of the Competence-Based Curriculum (CBC) ( REB, 2015b ) needs classroom instructional practices that motivate learners the most to like the chemistry daily class activities.…”
Section: Introductionmentioning
confidence: 99%